The influence of contaminant particles and filtration regime on fibrous mist-filter performance - Bredin, Arne (Curtin University, 2012)
This thesis comprehensively examined the kinetics of sooty oil-mist filtration under realistic conditions, such as found in diesel engines. The work developed many novel test methods and apparatuses, for soot-in oil analysis, filter soot analysis, filter testing under discontinuous conditions, and filter cleaning. Several new phenomena which occur in such filters were discovered, which were found to be due to airflow and capillary forces in the filter. The influence of soot was also comprehensively studied.